Tumor Budding Is an Independent Adverse Prognostic Factor in Pancreatic Ductal Adenocarcinoma. (April 2015) - O'Connor, Kate; Li-Chang, Hector H.; Kalloger, Steven E.; Peixoto, Renata D.; Webber, Douglas L.; Owen, David A.; Driman, David K.; Kirsch, Richard; Serra, Stefano; Scudamore, Charles H.; Renouf, Daniel J.; Schaeffer, David F.
<x xml:space="preserve">Abstract</x> Tumor budding is a well-established adverse prognostic factor in colorectal cancer. However, the significance and diagnostic reproducibility of budding in pancreatic carcinoma requires further study. We aimed to assess the prognostic significance of tumor budding in pancreatic ductal adenocarcinoma, determine its relationship with other clinicopathologic features, and assess interobserver variability in its diagnosis. Tumor budding was assessed in 192 archival cases of pancreatic ductal adenocarcinoma using hematoxylin and eosin (H&E) sections; tumor buds were defined as single cells or nonglandular clusters composed of <5 cells. The presence of budding was determined through assessment of all tumor-containing slides, and associations with clinicopathologic features and outcomes were analyzed. Six gastrointestinal pathologists participated in an interobserver variability study of 120 images of consecutive tumor slides stained with H&E and cytokeratin. Budding was present in 168 of 192 cases and was associated with decreased overall survival (P=0.001). On multivariable analysis, tumor budding was prognostically significantly independent of stage, grade, tumor size, nodal status, lymphovascular invasion, and perineural invasion. There was substantial agreement among pathologists in assessing the presence of tumor budding using both H&E (K=0.63) and cytokeratin (K=0.63) stains. The presence of tumor budding is an independent adverse prognostic factor in pancreatic ductal carcinoma. The assessment of budding with H&E is reliable and could be used to better risk stratify patients with pancreatic ductal adenocarcinoma.